Endothelium-dependent vasorelaxation effects of F5 fraction of Crinum amabile chloroform extract - Lim, Chung Pin; Fei, Yam Mun; Asmawi, Mohd. Zaini; Chin, VoonKin; Khairuddin, Nurul-Hayah; Yong, Yoke Keong; Lawal, Mukhtar Gambo; Basir, Rusliza (Springer Science and Business Media, 2023)
Background: Vascular dysfunction can lead to many health problems including hypertension and heart disease. The complexities of vascular dysfunction and vascular disorder-related diseases have prompted the search for many new biologically active compounds in the efforts of resolving the problems. Previous studies have shown that Amaryllidaceae alkaloids exert multiple biological activities, including the vasorelaxation effect. Crinum amabile, which is a family member of Amaryllidaceae, is believed to possess a promising pharmacological activity as a vasorelaxant.